Quantifying the global solar wind-magnetosphere interaction with the Solar-Terrestrial Observer for the Response of the Magnetosphere (STORM) mission concept - Sibeck, David G.; Murphy, Kyle R.; Porter, F. Scott; Connor, Hyunju K.; Walsh, Brian M.; Kuntz, Kip D.; Zesta, Eftyhia; Valek, Phil; Baker, Charles L.; Goldstein, Jerry; Frey, Harald; Hsieh, Syau-Yun; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Much of what we know about the solar wind’s interaction with the Earth’s magnetosphere has been gained from isolated in-situ measurements by single or multiple spacecraft. Based on their observations, we know that reconnection, whether on the dayside magnetopause or deep within the Earth’s magnetotail, controls the bulk flow of solar wind energy into and through the global system and that nightside activity provides the energized particles that power geomagnetic storms. But by their very nature these isolated in situ measurements cannot provide an instantaneous global view of the entire system or its cross-scale dynamics. To fully quantify the dynamics of the coupled solar wind-magnetosphere requires comprehensive end-to-end global imaging of the key plasma structures that comprise the magnetosphere which have spatial resolutions that exceeds anything possible with multi-point or constellation situ measurements. Global, end-to-end, imaging provides the pathway to understanding the system as a whole, its constituent parts, and its cross-scale processes on a continuous basis, as needed to quantify the flow of solar wind energy through the global magnetospheric system. This paper describes how a comprehensively-instrumented single spacecraft in a high-altitude, high-inclination orbit coupled with ground-based instruments provides the essential observations needed to track and quantify the flow of solar wind energy through the magnetosphere. This includes observations of the solar wind plasma and magnetic field input, the magnetopause location in soft X-rays, the auroral oval in far ultraviolet, the ring current in energetic neutrals, the plasmasphere in extreme ultraviolet, the exosphere in Lyman-alpha, and the microstructure of the nightside auroral oval from ground-based all sky cameras.